Minimizing Infection in a Topology using Mathematical Programming - Ataide, Wesly C.; Castellucci, Pedro B.; Franco, Álvaro J. P.; Santiago, Rafael de (Anais do Encontro de Teoria da Computação (ETC); 2022: Anais do VII Encontro de Teoria da Computação, 2022)
Minimizing the spread of an infection is a key strategy for controlling an epidemic. In urban regions, the spread can be reduced by restricting movement between adjacent districts. We propose a non-linear integer programming model to minimize the number of infected people in a network. The network considers the relations between districts and the movement of people in a city. We develop methods to build and improve solutions. The model and the methods are evaluated on an instance based on real data. Finally, the results indicate how challenging the problem is from an optimization and numeric perspective.